Incidence, predictors and prognostic implications of bleeding complicating primary percutaneous coronary intervention - Matić Dragan M.; Ašanin Milika R.; Stanković Sanja Đ.; Mrdović Igor B.; Marinković Jelena M.; Kočev Nikola I.; Antonijević Nebojša M.; Marjanović Marija M.; Nešić Zorica I.; Prostran Milica S.; Stanković Goran R. (Vojnosanitetski Pregled, 2015)
Background/Aim. Data about bleeding complicating primary percutaneous coronary intervention (PCI) are more frequently obtained from randomized clinical trials on patients with acute coronary syndromes (ACS), but less frequently from surveys or registries on patients with STelevation myocardial infarction (STEMI). The aim of this study was to investigate the incidence, predictors and prognostic impact of in-hospital major bleeding in the population of unselected real-world patients with acute STEMI undergoing primary PCI. Methods. All consecutive patients presenting with STEMI who underwent primary PCI at a single large tertiary healthcare center between January 2005 and July 2009, were studied. Major bleeding was defined according to the Global Use of Strategies to Open Occluded Coronary Arteries (GUSTO) study criteria. We examined the association between in-hospital major bleeding and death or major adverse cardiac events (MACE) in patients treated with PCI. The primary outcomes were in-hospital and 6-month mortality and MACE. Results. Of the 770 STEMI patients treated with primary PCI, in-hospital major bleeding occurred in 32 (4.2%) patients. Independent predictors of major bleeding were advanced age (≥ 65 years), female gender, baseline anemia and elevated white blood cell (WBC) count and signs of congestive heart failure at admission (Killip class II-IV). In-hospital and 6-month mortality and MACE rates were more than 2.5-fold-higher in patients who developed major bleeding compared with those who did not. Major bleeding was a predictor of 6- month MACE, independent of a few risk factors (previous MI, previous PCI, diabetes mellitus and hypertension); (OR = 3.02; 95% CI for OR 1.20-7.61; p = 0.019), but was not a true independent predictor of MACE and mortality in the fully adjusted models. Conclusion: Patients of advanced age, female gender, with baseline anemia and elevated WBC count and those with Killip class II-IV at presentation are at particularly high risk of bleeding after primary PCI. Bleeding is associated with adverse outcome and may be an important marker of patient frailty, but it is not a true independent predictor of mortality/MACE.